Minimally Invasive Coronary Revascularisation Surgery: A Focused Review of the Available Literature - Karel M Van Praet; Markus Kofler; Timo Z Nazari Shafti; Alaa Abd El Al; Antonia van Kampen; Andrea Amabile; Gianluca Torregrossa; Jörg Kempfert; Volkmar Falk; Husam H Balkhy; Stephan Jacobs (Interventional Cardiology: Reviews, Research, Resources)
Minimally invasive coronary revascularisation was originally developed in the mid 1990s as minimally invasive direct coronary artery bypass (MIDCAB) grafting is a less invasive approach compared to conventional coronary artery bypass grafting (CABG) to address targets in the left anterior descending coronary artery (LAD). Since then, MIDCAB has evolved with the adoption of a robotic platform and the possibility to perform multivessel bypass procedures. Minimally invasive coronary revascularisation surgery also allows for a combination between the benefits of CABG and percutaneous coronary interventions for non-LAD lesions – a hybrid approach. Hybrid coronary revascularisation results in fewer blood transfusions, shorter hospital stay, decreased ventilation times and patients return to work sooner when compared to conventional CABG. This article reviews the available literature, describes standard approaches and considers topics, such as limited access procedures, indications and patient selection, diagnostics and imaging, techniques, anastomotic devices, hybrid coronary revascularisation and outcome analysis.